2018
DOI: 10.1186/s12917-018-1685-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring antigen-specific responses in Mycobacterium bovis-infected warthogs (Phacochoerus africanus) using the intradermal tuberculin test

Abstract: BackgroundBovine tuberculosis (bTB) caused by Mycobacterium bovis has previously been diagnosed in warthogs and infection can be highly prevalent (> 30%) in endemic areas. Thus, warthogs could potentially be an important species to consider as sentinels for disease surveillance. However, disease surveillance is dependent on availability of accurate diagnostic assays and only a few diagnostic tests have been investigated for warthogs. Furthermore, the tests that have been used in this species require laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…One of the major problems for policy makers is identifying the main beneficiaries of any programme, simply because there are so many worthy candidates. In recent years, and driven by the need to better understand the disease, there have been many studies reporting new TB diagnostic tests for a variety of high value animal species (173182). Knowledge of the extent of the disease in these animals is the first step in addressing the problem, which may prove to be very costly.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major problems for policy makers is identifying the main beneficiaries of any programme, simply because there are so many worthy candidates. In recent years, and driven by the need to better understand the disease, there have been many studies reporting new TB diagnostic tests for a variety of high value animal species (173182). Knowledge of the extent of the disease in these animals is the first step in addressing the problem, which may prove to be very costly.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic organisms (categorized into bacteria, parasites, and viruses) specified in the 148 papers in the dataset. Associated diseases and clinical symptoms recorded in the 148 papers in the dataset.DiseasesBabesiosis[54]; bovine tuberculosis[29,30,[32][33][34]37,47,52,62,64,71,[97][98][99]; echinococcosis…”
mentioning
confidence: 99%
“…The single comparative intradermal tuberculin test (SCITT) relies on stimulating a CMI response in vivo with the intradermal injection of bovine and avian PPDs, after which a memory response is measured by a delayed-type hypersensitivity reaction. The SCITT is applied across multiple wildlife species including African buffalo, African wild dog, African lion, cheetah, leopard, antelope, and common warthog, however, validation has only been performed in a few of these species ( 70 , 74 , 77 ).…”
Section: Indirect Detectionmentioning
confidence: 99%
“…The need to calculate a SCITT species-specific cut-off value with appropriate study cohorts was highlighted in a study in which previously published criteria used to interpret SCITT for lions led to false positive results in 54% of animals tested ( 70 , 71 ). The study by Roos et al ( 74 ) in a bTB endemic cohort of common warthogs demonstrated that M. bovis -infected animals develop a measurable delayed-type hypersensitivity reaction to M. bovis PPD and the sensitivity and specificity of the SCITT, using common warthog-specific cut-off values, were 81 and 100%, respectively ( 74 ). Currently, the SCITT is performed in African buffaloes using the interpretation criteria for cattle, leading to suboptimal sensitivity ( 78 ).…”
Section: Indirect Detectionmentioning
confidence: 99%